Comparison of butorphanol-drotaverine versus tramadol-drotaverine as labour analgesics: an observational comparative study - Abid, Zarnain; Yousuf, Sumaira; Qureshi, Farheen; Rizvi, Syed Masuma; Ommid, Mohammad; Qureshi, Farha; Masood, Ashfaq (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Labour pain is a significant challenge in obstetric care, with effective pain management being essential for maternal well-being and labor outcomes. Epidural analgesia, the gold standard, is often inaccessible in resource-limited settings. Parenteral opioids like butorphanol and tramadol, combined with drotaverine, may provide an effective, low-cost alternative. To compare the effectiveness of butorphanol-drotaverine versus tramadol-drotaverine as labour analgesics in terms of maternal pain relief, labour outcomes and fetal outcomes. Methods: This observational, prospective, single-center study was done on 300 low-risk primigravid women in active labor where Butorphanol 1 mg+Drotaverine 40 mg was given to 150 patients (Group B) and Tramadol 100 mg+Drotaverine 40 mg was given to another 150 patients (Group T). Maternal pain was assessed using the Visual Analog Scale (VAS) at various time intervals. Labor progress, mode of delivery and side effects were monitored, along with fetal outcomes including Apgar scores and NICU admissions. Results: Both analgesic combinations provided effective pain relief, with Butorphanol providing quicker pain relief while as more sustained pain reduction was obtained with Tramadol. However, there were no significant differences in labor duration, mode of delivery or neonatal outcomes. Nausea was more common in the Tramadol group. Both drugs were well-tolerated, with minimal adverse effects. Conclusions: Both Butorphanol and Tramadol are effective for labor analgesia, with Butorphanol providing faster pain relief. These opioids offer a cost-effective alternative to epidural analgesia, especially in resource-limited settings, ensuring access to pain relief for all women during labor.